The influence of motivation on elementary school students' interest in sports - Prasandi, Aldiyas prasandi; Budiana, Dian; Anira, Anira (Hanoman Journal: Physical Education and Sport, 2024)
This research explores the influence of motivation on elementary school students' interest in sports. Motivation, as the main trigger of behavior, plays an important role in shaping students' interest in sports activities. ByÂ referring to the motivation theory of B.F. Skinner and the concept of self-actualization needs by Abraham Maslow, this research aims to deepen understanding of how motivation, both intrinsic and extrinsic, can shape students' interests. The research method used is a cross-sectional analytical study with a quantitative approach. Data was collected from Grade 4 elementary school students through the distribution of the Self-Motivation Inventory for Students (SIMS) questionnaire. Data analysis was carried out using descriptive statistical methods and the Pearson correlation test. The results of the analysis show that the majority of students have varying levels of motivation, with intrinsic motivation dominating. However, variations in extrinsic motivation were also seen, indicating the role of external factors in shaping student interest. These findings illustrate a significant positive relationship between students' level of motivation and their interest in exercise. The discussion includes factors that influence student interest, such as support from parents, peers, and the school environment. Understanding the role of intrinsic and extrinsic motivation provides further insight, and educational context has been shown to play an important role in shaping student motivation and interest. This research makes an important contribution in understanding the relationship between elementary school students' motivation and interest in sports. The proposed suggestions involve developing motivational programs, the role of parents, diversifying sports programs, health education, improving sports facilities, teacher training, and continuous monitoring. It is hoped that the implementation of these suggestions can create an educational environment that supports the development of student health and fitness at the elementary level.